THE PROCESS OF INCLUSION OF NEOLOGISMS INTO UZBEK LANGUAGE AND ITS ROLE IN THE LIFE OF SOCIETY - Alieva, Navruza; Mukhtoralieva, Fotima (Innovative Development in Educational Activities, 2023)
The article provides brief information about the methods and history of the Uzbek language’s development. The role of neologisms in the enrichment of our language and the processes of their introduction into our language are discussed. With the help of the analysis of examples, aspects of relationship of neologisms with social life are considered.